Shaykh Mutawalli al-Sha'rawi's Views About Tafsir and I'jaz al-Qur'an: (Descriptive-Analysis Study) - Kusroni Kusroni (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
This paper discusses the views of Shaikh Mutawalli al-Sha'rawi about the interpretation and i'jaz al-Qur'an contained in his book titled al-Tafsir al-Sha'rawi or Khawa> tir al-Sha'rawi. al-Sha'rawi is known as one of the leading modern scholars giving great attention and defense of the Qur'an. His attention to the Qur'an evidently appears in his commentary, a collection of lectures, sermons and studies in various pulpits and scientific forums. The method of delivering ideas taken by al-Sha'rawi in this work is by asking a number of questions about the existence of the i'jaz al-Qur'an, then he gives simple but argumentative answers, both aqliyah and naqliyah. Therefore, from here we know how his views related to interpretation and i'jaz al-Qur'an. Al-Sha'rawi argues that, the prophet of Muhammad  is the person who is most worthy of interpreting the Qur'an, because to him al-Qur'an was revealed. So he knows and practices it, and from it the mu‘jizat of the Qur'an was manifested. According to him, the mu‘jizat of the Qur'an is evolutionary and evolves with the times and with the progress of modern science and civilization.[يتكلم هذا الموضوع عن موقف الشيخ متولي الشعراوي حول القرآن وما يتعلق به من تفسير وإعجاز وغيره المكتوب فى كتابه المسمى بـ "التفسير الشعراوي" أوبـ "خواطر الشعراوي".ومما لا شك فيه أن هذا الشيخ الكبير يُعَدّ من جهابذة العلماء المعاصرين الذين يهتمون بالدفاع عن القرآن دفاعا قوياً. ويظهر هذا الدفاع عندما نلاحظ هذا الكتاب الذي هو منتخبات ومقتطفات مما ألقاه الشيخ الشعراوي خلال محاضرته وخُطبه ودروسه في البرامج والمناسبات المختلفة. والجدير بالذكر أنّ المنهج الذي سلك به الشيخ هو الإتيان بالتسائلات حول القرآن ما يدل على الترييب والتشكيك فى الجانب الإعجازي للقرآن الكريم, ثم يأتي هو بالأجوبة الصارحة مع الحجج القاطعة. رغم أنه أتى بالحجة النقليةالكثيرة لكنه في نفس الوقت أورد الأدلة العقلية. ومن ثم يظهرلنا أفكاره العلمية حول القرآن الكريم تفسيرا وإعجازا. ويرى الشيخ أن أولى الناس بالتفسير هوالرسول ﷺ لأنه عليه نزل وبه علم وعمل وله ظهرت معجزاته. وأن الإعجاز القرآني عنده يتطوّر مع تطوّر الأزمان والعلوم العصرية والثقافة والحضارة.]